2021
DOI: 10.1111/inr.12658
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nursing professionals in Cambodia: strategies to overcome underpinning challenges

Abstract: Aims To elucidate (i) the challenges and constraints in the development and implementation of the regulatory framework for nursing professionals in Cambodia and (ii) the specific strategies adopted to address the challenges experienced in Cambodia. Introduction The health workforce will be critical to achieving the health‐related and wider Sustainable Development Goals in the years up to 2030. Background In 2006, the countries of the Association of Southeast Asian Nations signed a Mutual Recognition Arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The limited vocabulary of the Khmer language and the issue that English is not commonly used in the country may have influenced the limited nuanced translation from English into Khmer. This is consistent with a recent study from Cambodia in which the translation from English to Khmer was a big challenge due to unfamiliarity with nuanced technical jargon in the cultural and linguistic settings [42]. This is also consistent with other studies that have shown how terms can be influenced by culture and render translations conceptually different [21,43].…”
Section: Plos Onesupporting
confidence: 92%
“…The limited vocabulary of the Khmer language and the issue that English is not commonly used in the country may have influenced the limited nuanced translation from English into Khmer. This is consistent with a recent study from Cambodia in which the translation from English to Khmer was a big challenge due to unfamiliarity with nuanced technical jargon in the cultural and linguistic settings [42]. This is also consistent with other studies that have shown how terms can be influenced by culture and render translations conceptually different [21,43].…”
Section: Plos Onesupporting
confidence: 92%
“…An interview guide for the IIs and FGDs was developed by the authors by adapting the interview guides developed by Matsuoka et al, aiming to identify barriers to the use of health services [20] and intending to elucidate challenges and constraints in the development and implementation of the regulatory framework for nursing professionals with a viewpoint of the ecological model in the Mekong region [21]. Then, the guide was translated into Vietnamese, Burmese, and Nepali by the assistants, back-translated by different assistants, pilot-tested, and finalized before data collection.…”
Section: Data Collectionmentioning
confidence: 99%
“…Technical assistance from development partners has had synergistic effects by consistently promoting the involvement of nursing leaders in the administration, education, and clinical practice in establishing a functional regulatory system for nursing professionals and providing services in resource-limited settings for 20 years. Nursing leaders are essential in driving implementation and linking all necessary regulatory functions (11,12). The development of human resources in low-and middle-income countries requires the application of edge-pulling (leadership development) and bottom-up (quality improvement of the mass population) strategies based on long-and middle-term perspectives (13).…”
Section: Further Improvement and Necessary Investment For Nursing Hum...mentioning
confidence: 99%